Effects of Selective employment tax : final report - Reddaway, William Brian; Glynn, D. R.; Sugden, J. D. (Cambridge, England : University Press, 1973)
The basic objective of the selective employment tax was to impose on employers in certain industries a tax of a certain amount per week for each person they employed (varying accordingly as the employee was adult or juvenile, and male or female).
Includes bibliographical references.
ne 24/01/2019
Loans
Keywords: Payroll tax; Employment tax